2001
DOI: 10.3354/meps210149
|View full text |Cite
|
Sign up to set email alerts
|

Threat to macroalgal diversity: effects of the introduced green alga Caulerpa racemosa in the Mediterranean

Abstract: ) C. racemosa overgrew native macroalgal species within 4 mo. As a consequence, phytobenthic community structure deeply changed: species cover, number and diversity greatly decreased. Furthermore, the relative importance among vegetation layers of the macroalgal assemblage changed: turf and encrusting species were deeply affected while erect species survived after 1 yr of the invasion. During the period from December to May, when both cover and biomass of C. racemosa diminished, the macroalgal community did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
120
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 32 publications
10
120
1
2
Order By: Relevance
“…Studies to date have shown their effect on native macroflora and macrofauna (e.g., Piazzi et al, 2001;Balata et al, 2004;Cebrian et al, 2012;Deudero et al, 2010;Marbà et al, 2014) in terms of compositional changes and/or abundance shifts. However, they also have more cryptic impacts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to date have shown their effect on native macroflora and macrofauna (e.g., Piazzi et al, 2001;Balata et al, 2004;Cebrian et al, 2012;Deudero et al, 2010;Marbà et al, 2014) in terms of compositional changes and/or abundance shifts. However, they also have more cryptic impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Another side of invasion biology is the assessment of the impact of alien species on native assemblages. This is usually performed by traditional community analysis methods, involving sampling, sorting, identification, and preparation of qualitative and/or quantitative inventories (e.g., Piazzi et al, 2001;Balata et al, 2004;Box et al, 2010). These tasks are time-consuming, strongly dependent on available taxonomic expertise, and in practice applied only to the analysis of the larger elements of the fauna and flora which constitute only a minor fraction of the diversity present (Blaxter, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce time and resources for taxonomic determination of species, several surrogates have been suggested elsewhere (e.g. Phillips et al 1997;Piazzi et al 2001). A crucial attribute of surrogates has to be that they adequately represent pattern of spatial variability in assemblages at multiple spatial scales (Smale 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Helgol Mar Res (2013) 67:191-201 199 In contrast for multivariate analyses, this hypothesis was rejected except for the spatial scale of area. Macroalgae are useful organisms to monitor the environmental quality and to detect impacts due to anthropogenic activities (Piazzi et al 2001;Díez et al 2009). In order to reduce time and resources for taxonomic determination of species, several surrogates have been suggested elsewhere (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation